Economic Recession in Nigeria: Lessons from Umar Ibn Al-Khattab’s Economic Policies - Bello, Khalid Ishola (Asy-Syari'ah, 2024)
Abstract: Economic conditions are dynamic and can shift from prosperity to adversity, affecting individuals and nations alike. This paper examines the socio-economic recession during the early Islamic era under the leadership of Umar ibn Al-Khattab, exploring its causes, remedies, and eventual recovery. Umar's governance, marked by compassionate leadership, adaptive policies, and resource prioritization, provides valuable lessons for addressing contemporary economic challenges. Nigeria, facing economic recessions characterized by unemployment, inflation, and resource mismanagement, can use these lessons to mitigate its economic woes. The study employs a historical and content analysis of early Islamic economic policies, a comparative analysis of Nigeria's current challenges, and policy reviews. It highlights the need for empathetic leadership, legislative flexibility, effective resource allocation, and integration of Islamic social finance mechanisms, such as zakāt and waqf, into Nigeria's socioeconomic framework. Nigeria can enhance its economic resilience and inclusivity by fostering transparency, social justice, and collaboration while addressing systemic inequities.